A mutation in LXRα uncovers a role for cholesterol sensing in limiting metabolic dysfunction-associated steatohepatitis - Alexis T. Clark; Lillian Russo-Savage; Luke A. Ashton; Niki Haghshenas; Nicolas A. Amselle; Ira G. Schulman (Nature Communications)
Abstract Liver x receptor alpha (LXRα) functions as an intracellular cholesterol sensor that regulates lipid metabolism at the transcriptional level in response to the direct binding of cholesterol derivatives. We have generated mice with a mutation in LXRα that reduces activity in response to endogenous cholesterol derived LXR ligands while still allowing transcriptional activation by synthetic agonists. The mutant LXRα functions as a dominant negative that shuts down cholesterol sensing. When fed a high fat, high cholesterol diet LXRα mutant mice rapidly develop pathologies associated with Metabolic Dysfunction-Associated Steatohepatitis (MASH) including ballooning hepatocytes, liver inflammation, and fibrosis. Strikingly LXRα mutant mice have decreased liver triglycerides but increased liver cholesterol. Therefore, elevated cholesterol in the liver may play a critical role in the development of MASH. Reengaging LXR signaling by treatment with synthetic agonist reverses MASH in LXRα mutant mice suggesting that LXRα normally functions to impede the development of liver disease.